Morvan's syndrome associated with antibodies to multiple components of the voltage-gated potassium channel complex. - Loukaides, P; Schiza, N; Pettingill, P; Palazis, L; Vounou, E; Vincent, A; Kleopa, K (2012)
We describe a patient presenting with a combination of muscle fasciculations, paresthesias, hyperhidrosis, as well as insomnia, agitation and confusion. He went on to develop psychosis and respiratory failure requiring intensive care. Electromyography confirmed the presence of neuromyotonia and CSF showed mild pleocytosis. Routine testing for voltage-gated potassium channel complex (VGKC-complex) antibodies was highly positive, confirming the clinical diagnosis of Morvan's syndrome. The patient improved after treatment with intravenous immunoglobulin and methylprednisolone. Further investigation of the antigenic targets using immunohistochemistry and cell-based assays revealed that he had autoantibodies targeting Lgi1, Caspr2 and Contactin-2/Tag-1, all proteins known to be complexed with VGKC in peripheral nerves and CNS. This is the first case of Morvan's syndrome from Cyprus and illustrates the clinical features as well as the emerging complexity of antigenic targets involved in the pathogenesis.